Potential damaging mutation in LRP5 from genome sequencing of the first reported chimpanzee with the Chiari malformation. Issue 1 (December 2017) - Solis-Moruno, Manuel; de Manuel, Marc; Hernandez-Rodriguez, Jessica; Fontsere, Claudia; Gomara-Castaño, Alba; Valsera-Naranjo, Cristina; Crailsheim, Dietmar; Navarro, Arcadi; Llorente, Miquel; Riera, Laura; Feliu-Olleta, Olga; Marques-Bonet, Tomas
Abstract The genusPan is the closest related to humans (Homo sapiens ) and it includes two species:Pan troglodytes (chimpanzees) andPan paniscus (bonobos). Different characteristics, some of biomedical aspect, separate them from us. For instance, some common human medical conditions are rare in chimpanzees (menopause, Alzheimer disease) although it is unclear to which extent longevity plays an active role in these differences. However, both humans and chimpanzees present similar pathologies, thus, understanding traits in chimpanzees can help unravel the molecular basis of human conditions. Here, we sequenced the genome of Nico, a central chimpanzee diagnosed with a particular biomedical condition, the Chiari malformation. We performed a variant calling analysis comparing his genome to 25 whole genomes from healthy individuals (bonobos and chimpanzees), and after predicting the effects of the genetic variants, we looked for genes within the OMIM database. We found a novel, private, predicted as damaging mutation in Nico inLRP5, a gene related to bone density alteration pathologies, and we suggest a link between this mutation and his Chiari malformation as previously shown in humans. Our results reinforce the idea that a comparison between humans and chimpanzees can be established in this genetic frame of common diseases.